2021
DOI: 10.31729/jnma.6463
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease in Patients Visiting a Tertiary Care Dental Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Periodontitis is chronic disease leading to tooth loss. Oral hygiene practices combined with regular dental examinations keep oral cavity disease free and maintain periodontal health. The primary objective was to find out the prevalence of periodontal disease of patients measured by the Simplified Oral Hygiene Index and Community Periodontal Index. Methods: This descriptive cross-sectional study was conducted in department of Periodontics of a tertiary care dental hospital from April to June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…However, a few studies contradict the present finding, which found no significant association between periodontal health and length of illness. It also showed that the patient's TB status did not affect periodontal health 1,3,6,13,21 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a few studies contradict the present finding, which found no significant association between periodontal health and length of illness. It also showed that the patient's TB status did not affect periodontal health 1,3,6,13,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors such as a history of TB, chronic bronchitis, neoplasms, diabetes, HIV, alcoholism, and drug addiction are equally important to consider in patients suspected of suffering from TB 16 . Numerous research has attempted to link periodontal disease to tuberculosis, but the findings have been contradictory 1,[3][4][5]7,14 . Studies have previously been proposed that link periodontal disease to a range of systemic ailments, including diabetes mellitus 17 , coronary artery disease 18 , stroke, and respiratory illnesses 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations